2022
DOI: 10.5624/isd.20210277
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical variations of the ethmoid sinuses and their association with health or pathology of the ethmoid and maxillary sinuses in a Southern Chinese population: An analysis using cone-beam computed tomography

Abstract: Purpose The aim of this study was to evaluate the prevalence of clinically relevant anatomical variations of the ethmoid sinuses and their potential association with ethmoid and maxillary sinus pathologies on cone-beam computed tomography (CBCT) scans. Additionally, potential associations with different sides and demographic factors, including age and sex, were evaluated. Materials and Methods In total, 273 CBCT scans with complete ethmoid and maxillary sinuses were ana… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…This study estimated the prevalence of Haller cells in CBCT images almost high and about 56.7%. In some studies, an extremely variable range (2%–70.3%) has been reported for the prevalence of Haller cells [ 8 , 11 – 25 ]. Mathew et al [ 6 ] reported a 60% prevalence for Haller cells and Khojastepour et al [ 26 ] reported 68%, which are close to our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study estimated the prevalence of Haller cells in CBCT images almost high and about 56.7%. In some studies, an extremely variable range (2%–70.3%) has been reported for the prevalence of Haller cells [ 8 , 11 – 25 ]. Mathew et al [ 6 ] reported a 60% prevalence for Haller cells and Khojastepour et al [ 26 ] reported 68%, which are close to our study.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of Haller cells in CT examinations has a wide range [ 1 , 3 , 7 ]. Hui et al indicated that the prevalence of Haller cell is 29.5% and there was no significant relation between the presence of Haller cell and maxillary sinus pathologies [ 8 ]. Some studies showed a significant relationship between Haller cell size (>3 mm) and orbital floor dehiscence; nevertheless, there is no definite information on this matter [ 2 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…This was not documented in previous reports of EMSs. 8,26 THE MAXILLARY BULLA Both Ozcan et al (2008) 7 and Sirikci et al (2004) 9 found ethmomaxillary septa convex towards the MS. These were bona fide cases with maxillary bullae produced by the EMS.…”
Section: Duplications Of the Maxillary Sinusmentioning
confidence: 98%
“…Interestingly, different studies on the EMS reported it posterosuperior to the MS, [7][8][9]13,26,27 therefore, with a horizontal or oblique position of the ethmomaxillary septum separating the MS and the EMS. This septum was indicated by Liu et al (2018) 8 as "ethmomaxillary plate."…”
Section: The Ethmomaxillary Septummentioning
confidence: 99%
See 1 more Smart Citation